Factors Influencing Empyema in Children - Cissy B. Kartasasmita; Oma Rosmayudi; Rita Wahyunarti (Indonesian Pediatric Society, 1988)
Incidence of empyema in children at Hasan Sadikin General Hospital is still high, commensurate with the high number of cases of pneumonia. Thirty-seven children with empyema were studied from July 1984 to December 1985; 20 of them were females and 17 males with the age ranging between 5 months and 12 years. Three patients (8.1 %) had loculated fluid as observed on chest roentgenographs; the remainder had empyema sinistra and dextra at 43.2% and 48.6% respectively. More than 50% of the patients were undernourished (56. 7%), 5 of whom were marasmic. On admission, 89.2% complained of dyspnea, 24.3% of cough, 16.2% of high fever and 10.8% of chest pain. All patients suffered from acute respiratory tract injection (ARI) 7 to 30 days before admission, 70.3% of whom did not receive adequate medication and 5 individuals received no treatment at all. Chest tube drainage was performed on 34 patients. In the study, 3 patients died (8.1%) due to sepsis. All recovered patients had pleural thickening on chest roentgenographs on discharge. The role of under nutrition, delay of medication and inadequate treatment of ARI seemed to have an1 influence on empyema in the patients observed.